THE INFLUENCE OF SEX TOWARD THE COMPREHENSION READING ABILITY OF CLASS V STUDENTS IN THE ELEMENTARY SCHOOL OF PANJER VILLAGE - Dwi Pungky Ari Sandhi; Diyani Ayu Karimizzah; Diah Monitasari; Suhartono Suhartono (Universitas Sebelas Maret, 2018)
Reading is a skill needed to get knowledge. To understand the contents of a reading, it is necessary to have comprehension reading ability. Faktors that influence the reading comprehension ability are physiological, intellectual, environmental and psychological faktors. Physiological faktors include physical health, neurological consizderations and sex. The focus of this research is on the influence of sex. This research uses a correlational method in which the populations used are fifth grade students of primary schools in Panjer village, Kebumen district with a sample of 4 classes from 4 elementary schools. The results of this research indicate that female students have better comprehension reading ability than male students.